Tehillah le-Moshe : Biblical and Judaic Studies in Honor of Moshe Greenberg - Greenberg, Moshe; Cogan, Mordechai; Eichler, Barry L.; Tigay, Jeffrey H. (Eisenbrauns, 1997)
Forty-five scholars here combine their skills in tribute to their colleague, teacher, and friend. This collection includes 27 English and 18 Hebrew essays on literary criticism, rabbinic literature, Hebrew word studies, Septuagint, Qumran, textual criticism, and many other topics. Moshe Greenberg is perhaps best known for his commentary on Ezekiel in the Anchor Bible series.